The Principle of Checks and Balances in Islamic State Administration Studies - Yandy, Eza Tri; Tauvani, A Yuli; Sulaeman, Sulaeman; Yusuf, M.; Isa, Muhammad (Jurnal Mediasas: Media Ilmu Syari'ah dan Ahwal Al-Syakhsiyyah, 2024)
The principle of Checks and Balances is a concept of the constitutional system in Indonesia which is designed to create state stability because this concept emphasizes that existing power does not exceed limits and interestingly this concept has existed for a long time in Islamic state administration during the reign of the Prophet Muhammad SAW. This research aims to explain the concept and practice of sharing power in Islamic state administration. The type of research used is normative legal research with a conceptual approach because the author wants to explain how the principle of distribution of power in Islamic state administration is actually implemented. In this research, the author used primary data sources including legal regulations in Indonesia, and literature related to Siyasah fiqh, while secondary data was obtained through library literature in the form of books, journals or other research that can be used as a reference. The results of this research explain that the division of power in the government systems in Indonesia and Islam is compatible in that both systematically regulate power itself in an effort to avoid the behavior of authoritarian and tyrannical leaders. Power in Islamic government is known as legislative/sulthan at-tasri'iyah whose authority is to determine laws/cases and is tasked with supervising state finances, including planning, spending and controlling executive institutions. Sulthan tanfidziyah in an Islamic perspective uses the term Ulil Amri, led by the caliph or Amir, responsible for actualizing the rules of government. The sulthan qadhaiyyah judiciary is a judicial institution tasked with dealing with community problems from religious, social and political aspects, in carrying out its duties the Islamic judiciary is assisted by subordinate bodies, namely al-qadha, al-Hisbah, al-Mazhalim. [Abstrak: Prinsip Checks and Balances merupakan sebuah konsep system ketatanegaraan di Indonesia yang di desain untuk menciptakan stabilitas negara karena konsep ini menegaskan agar kekuasaan yang ada tidak melampaui batas dan menariknya konsep ini sudah ada sejak lama dalam ketatanegaraan Islam pada masa pemerintahan Rasulullah Muhammad SAW. Penelitian ini bertujuan untuk memaparkan bagaimana konsep dan praktik pembagian kekuasaan dalam ketatanegaraan Islam. Jenis penelitian yang digunakan adalah penelitian hukum normatif dengan pendekatan konseptual karena penulis ingin menguraikan bagaiman sebenarnya prinsip pembagian kekuasaan dalam ketatanegaraan Islam di jalankan. dalam penelitan ini penulis menggunakan sumber data primer diantaranya peraturan perundang-undangan di Indonesia, dan literatur yang berkaitan denga fiqh Siyasah, sedangkan data skunder di dapatkan melalui literatur perpustakaan dalam bentuk buku, jurnal atau penelitian lain yang dapat dijadikan rujukan. Hasil penelitian ini menjelaskan bahwa pembagian kekuasaan dalam sistem pemerintahan di Indonesia dan Islam memiliki kesesuaian yang keduanya sama-sama mengatur secara sistematis kekuasaan itu sendiri upaya menghindari prilaku pemimpin otoriter dan zhalim. Kekuasaan dalam pemerintahan Islam dikenal dengan istilah legislatif/sulthan at-tasri’iyah yang wewenangnya melakukan penetapan hukum/perkara serta bertugas melakukan pengawasan terhadap keuangan negara baik rancangan, pengeluaran dan sebagai kontrol lembaga eksekutif. Sulthan tanfidziyah dalam perspektif Islam menggunakan istilah Ulil Amri yang dipimpin oleh khalifah atau Amir, bertanggungjawab mengaktualisasikan aturan-aturan pada pemerintahan. Yudikatif sulthan qadhaiyyah iyalah lembaga peradilan bertugas menangani masalah masyarakat baik dari aspek agama, sosial dan politik, dalam menjalankan tugasnya peradilan Islam dibantu badan-badan dibawahnya yaitu al-qadha, al-Hisbah, al-Mazhalim.]